Pengaruh Game Edukatif Educaplay Terhadap Hasil Belajar Membaca Siswa Kelas X SMAN Negeri 1 Gowa - Isti Asrifah; Baharman; Ni Nengan Wirjani (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to describe the effect of Educaplay educational game on reading learning outcomes of students in class X.2 SMANi 1 Gowa. This research is a type of quantitative research with the research design used is One Group Pretest-Posttest Design. The research sample totalled 36 students. The instrument used in the study was a multiple choice test. Data analysis techniques used in this research are descriptive statistics and inferential statistics. The results showed that the motivation and understanding after using Educaplay educational games of class X.2 SMAN 1 Gowa students were categorised as quite good with an average score of 60.14. The motivation and understanding after using Educaplay educational game of students of class X.2 SMAN 1 Gowa is categorised as good with an average score of 79.86; (3) the result of hypothesis testing shows that the sig.(2-tailed) value is 0.000 <0.05. Thus, there is an effect of Educaplay educational game on the motivation and understanding of students of class X.2 SMA Negeri 1 Gowa.